Modelagem termodinâmica computacional de ligas multicomponentes cúbicas de corpo centrado para armazenagem de hidrogênio - Pedroso, Otávio Abreu (Universidade Federal de São Carlos, 2021)
Recently, multicomponent metal alloys for hydrogen storage have drawn attention due to the possibility of exploring a large compositional field, which can allow the control of storage properties by controlling the alloy composition, thus satisfying the needs for each application. The laboratory of hydrogen in metals at DEMa/UFSCar has vast experience in the synthesis, characterization, and evaluation of the properties of these alloys. The next step is to develop methods and models to predict the thermodynamic properties that determine their operating conditions (pressure and temperature for absorption/desorption) based solely on the chemical composition, aiming to improve the tools available to carry out the design of alloys for storage of hydrogen with suitable properties for different applications. Recently, Zepon et al. proposed a thermodynamic model to calculate pressure-composition-temperature (PCT) diagrams of multicomponent cubic body-centered alloys (CCC). of sites, and the enthalpy of the phases is modeled based on experimental data and calculated from ab initio through density functional theory (DFT). This master’s work aimed to add new chemical elements to the recently proposed model through DFT calculations and to develop an open code program for the calculation of PCT diagrams based on the model and the data obtained by DFT. The elements Mg, Al, Sc, Mn, Fe, Co, Cu, Zn, Mo, and Pd were incorporated into the model and their implementation in open-source software in the Python programming language. Using this software, the alloys reported in the literature were evaluated so that it was possible to observe that the alloys of the TiVNbCr system are better described by the model, in addition to the fact that some alloys containing Mg show a discrepancy between the crystal structure observed experimentally and those obtained by the model.
Computational thermodynamic modeling of body centered cubic multicomponent alloys for hydrogen storage
Keywords: Sustentabilidade; Energias renováveis; Armazenamento de hidrogênio; DFT; Ligas multicomponentes; Sustainability; Renewable energy; Hydrogen storage; Multicomponent alloys; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA